A comparative chromatography study of different Tel Spp. (Ipomoea Spp.) in Kuliyapitiya region, Kurunegala District, Sri Lanka - Wijayasinghe, L.S.G.; Dissanayake, D.M.H.D.B.; Priyadarshani, A.I.S.; Perera, P.K. (Faculty of Indigenous Medicine, University of Colombo, 2014)
"Tel" (Ipomoea species, Family Convolulacea) is a vine growing commonly in South Asia, East Africa, Asia Pacific and ...
Keywords: Impomoea spp; Flavonoids; TLC; Tel